VOCAL CHORDS LEARNING MODEL AT THE PRIMARY BASED ON THE NATION CHARACTER AND LOCAL VALUE - Jagar Lumbantoruan (International Conference on Languages and Arts, 2014)
Vocal chords learning model at the primary  based on the nation  character and local value, aims to nurture the learners of how to gain the skills of singing for the purpose of forming their strong character and enhancing the local value, as well. The implementation of character based vocal learning, starting from the song (lyric) mastery all out according to the rhythm and melody.Nurturing which is dealing with the nation character based development, can develop the learners’  five powers such as: Faith of God, Creation, Feeling, Idealism, and Artificial, which are implemented throughout belief and receiving, love and friendliness, empowering, straight action of nurturing, leading and role-modeling. The rhythm and melody mastery of the students can form their character of faith, disciplinary, and aware of the signals covered in the song. Finally, the strong character, faithfulness, disciplinary and awareness are nurtured in the learners’ personality, subconsciously or unsubconsciously.   Keywords: Vocal Learning, Character and Local Value.